The polyglot reading test (Experimental Form) - Wagner, Rudolph F. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The polyglot oral reading test was designed to test a student’s oral word recognition, Grades K through 3, and uses words which are conceptually equivalent in four languages: English, French, German and Spanish. The reading score obtained is a Grade Equivalency Score. Potentially, the test can be useful in research where an assessment of reading skills is needed for cross-cultural comparisons which in turn, might give insight into the reading process, reading disabilities and teaching methodologies as practiced in various countries.